Adsorption Study of Orange G Dye on Thermally Modified Rice Husk from Aqueous Medium: Study of Orange G Dye - Abdul Malik; Abbas Khan; Sana Ullah; Faisal Safi; Shakeel Ahmad; Naseem Ullah; Shakeel Ahmad Khan (Biological Sciences - PJSIR, 2023)
Thermal modification of rice husk in open air environment was carried out by burning of rice husk, followed by a heat action in tube furnace at 973 K0 for one hour. The material obtained was whitish in colour and termed as rice husk ash (RHA), which was applied to adsorbed the Orange G-dye from aqueous medium. The adsorption process was studied in various experimental conditions that could greatly affect the adsorption process. The optimum conditions for the maximum adsorption of dye, were investigated as; pH 4, temperature 303 K0 and 80mg/L of initial dye concentration containing 2g/L of the adsorbent concentration. At optimum conditions the dye removal was investigated as 57.6% with adsorption capacity 23.05 mg/g. Thermodynamic study indicated that the adsorption process is exothermic and spontaneous. Kinetic data for the adsorption of Orange-G on the RHA-adsorbent, best followed the pseudo-S second order kinetic model, whereas equilibrium experimental data is fit to Langmuir-model, suggested that adsorption of OG on RHA is a chemical adsorption.